MODERASI BERAGAMA DALAM PENDIDIKAN ISLAM: ANALISIS TAFSIR SURAH ĀLI ‘IMRĀN AYAT 64–110 DI ERA POLARISASI DIGITAL - Achmad Wildan Suyuti (Jurnal Manajemen Pendidikan, 2026)
A polarized digital ecosystem poses significant challenges for Islamic education in maintaining intra-communal solidarity (ukhuwah) and fostering interfaith dialogue. This study aims to analyze the messages of religious moderation, ukhuwah, and anti-fragmentation in Surah Āli ‘Imrān (64–110), and to formulate pedagogical principles and strategies for managing digital spaces It employs a qualitative library-based approach using thematic exegesis (mawḍū‘ī), integrated with empirical findings on digital polarization and moderation education.The study identifies four key themes: (1) kalimah sawā’ as a common ground for Muslim–People of the Book dialogue; (2) ukhuwah and the prohibition of division as the foundation of social cohesion; (3) dialogical and non-coercive da‘wah as a learning model; and (4) vigilance against misinformation and the importance of verification in digital literacy. The findings highlight that Islamic education must be implemented applicatively through curriculum strategies, teaching methods, and governance of digital interaction. The study contributes theoretically by enriching Qur’anic-based moderation discourse and social interaction theory, and practically by offering a ukhuwah-based and interfaith dialogue-oriented curriculum model relevant to the digital age.